Book of Abstracts Spanish Fluid Mechanics Conference 2025 - VV.AA. (3rd Spanish Fluid Mechanics Conference Organizing Committee., 2025)
Libro de resúmenes de las ponencias presentadas al SFMC25
Keywords: Mecánica de fluidos - Congresos; Fluid mechanics